Pemanfaatan Video Tiktok Alex Sebagai Media Pembelajaran Menulis Teks Prosedur di Kelas VII SMP Negeri 3 Singaraja - Ni Made Phidiya Yanuarita Maharani; Dewa Gede Budi Utama; Kadek Wirahyuni (Universitas Pendidikan Ganesha, 2026)
This study aims to describe the use of Alex's TikTok videos as a learning medium for writing procedural texts in seventh-grade students at SMP Negeri 3 Singaraja, to determine student responses, and to identify challenges faced by teachers. The study employed a qualitative descriptive method with observation, interviews, questionnaires, and documentation techniques. The results showed that Alex's TikTok videos were effective in helping students understand the structure and rules of procedural texts because they presented the steps visually, concisely, and clearly. Students' responses were positive; they found the learning more engaging, easier to understand, and increased their motivation to write. Challenges that arose included unstable internet connections, short video duration, and differences in students' abilities in comprehending audiovisual information. The study concluded that Alex's TikTok videos are a relevant and effective medium for improving students' procedural text writing skills and are suitable as an alternative digital-based learning medium.